Auditoría modalidad regular a la ESE Pio X del municipio de La Tebaida vigencia 2014 (2015)
The aim of the internship was the achievement of a regular audit to “la empresa social Del Estado, Hospital Pio X” from Tebaida, Quindío, considering the assessment and examination that the entities carry out. In this case, La Contraloría General del Quindío, to make sure of the operations of control and to express an integral report including the declaration on the account’s expiration date, organized by the opinion of the financial conditions, and the concept of the management, based on parameters established in “la Guía de Auditoría Territorial” adopted as the “Contraloría Departamental del Quindío” through Resolución No. 207 de diciembre 20 de 2012.